2021
DOI: 10.1371/journal.pone.0242645
|View full text |Cite
|
Sign up to set email alerts
|

Potential of in vivo- and in vitro-cultured entomopathogenic nematodes to infect Lobesia vanillana (Lepidoptera: Tortricidae) under laboratory conditions

Abstract: Entomopathogenic nematodes (EPNs) have been successfully applied as biological control agents against above ground and soil stages of insect pests. However, for commercial application, it is crucial to mass culture these nematodes using in vitro liquid culture technology, as it is not attainable when using susceptible insects as hosts. Lobesia vanillana (Lepidoptera: Tortricidae) is regarded a sporadic pest of wine grapes in South Africa. The in vivo- and in vitro-cultured South African EPNs, Steinernema yirga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
2
8
1
Order By: Relevance
“…This study showed that the EPNs could be effective biological control agents against EGVM larvae and pupae in vineyards. In agreement with previous studies against other tortricid species, including L. vanillana, EPN virulence differed among nematode species [35,38,39,41,42]. As observed for C. pomonella [38], our S. carpocapsae population resulted in being the most virulent against the various larval and pupal stages.…”
Section: Entomopathogenic Nematodes As Biological Control Agents Against Larvae and Pupae Of The European Grapevine Mothsupporting
confidence: 91%
See 4 more Smart Citations
“…This study showed that the EPNs could be effective biological control agents against EGVM larvae and pupae in vineyards. In agreement with previous studies against other tortricid species, including L. vanillana, EPN virulence differed among nematode species [35,38,39,41,42]. As observed for C. pomonella [38], our S. carpocapsae population resulted in being the most virulent against the various larval and pupal stages.…”
Section: Entomopathogenic Nematodes As Biological Control Agents Against Larvae and Pupae Of The European Grapevine Mothsupporting
confidence: 91%
“…On the contrary, S. carpocapsae and S. feltiae registered 100% and 80% L5 mortality, respectively, at the same time exposure. Overall, the efficacy of our EPN populations at 48 IJs per host against L. botrana obtained similar results to those observed for two South African EPN species against L. vanillana but employed 100 IJs per host [39]. Indeed, the efficacy of these two EPN species in the 50% lethal concentration estimations against L5 EGVM is notorious.…”
Section: Entomopathogenic Nematodes As Biological Control Agents Against Larvae and Pupae Of The European Grapevine Mothsupporting
confidence: 83%
See 3 more Smart Citations